Assessing the impact of teaching methods on student engagement in Tanzanian secondary schools: A comprehensive review - Lameck Mduwile, Peter; Lufunga, Janeth; Goswami, Dulumoni (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This research paper presents a comprehensive review of the impacts of various teaching methods on student engagement in Tanzanian secondary schools, while addressing the contextual challenges of the country’s educational system. Tanzanian schools continue to face persistent barriers such as large class sizes, limited instructional resources, and diverse socio-cultural factors that influence teaching and learning. To investigate these dynamics, the study employed a systematic literature review with qualitative insights gathered from 15 Tanzanian educators. Data collection instruments included semi-structured interviews, classroom observation checklists, and document analysis to ensure both depth and triangulation of findings. The results demonstrate that learner-centered methods, particularly inquiry-based and cooperative learning strategies, improve student engagement by approximately 20–30% compared to traditional lecture-based approaches. Furthermore, the integration of culturally responsive pedagogies and technology-enhanced instruction shows significant potential, although these approaches remain constrained by financial and infrastructural limitations. Based on the evidence, the paper recommends targeted teacher training programs, curriculum reforms that embed participatory methods and scalable, low-cost interventions that align with the Tanzanian context.